Effect of Health and Nutrition Education on Blood Pressure, Knowledge and Compliance among Hypertensive Patients in Bogor District, Indonesia: A Control Quasi-Experiment - Nurul Dina Rahmawati; Ratu Ayu Dewi Sartika; Hasbullah Thabrany (Indonesian Journal of Public Health Nutrition, 2022)
AbstractWith a high prevalence of hypertension (25.8% in 2013 and 34.1% in 2018), Indonesia currently deals with a tremendous health economic burden with the implementation of National Health Insurance (JKN).  Hypertension is known to lead to severe complications and productivity loss. This study aimed to evaluate the effect of health and nutrition education on blood pressure knowledge and compliance among hypertension patients. The study was conducted over a period of 6 months in Bogor District.  A total of 179 patients (64%) completed the study (intervention n = 88, control n = 91). Compared to the control group, patients in the intervention group showed a significant improvement of knowledge and compliance (p < 0.001), yet no significant difference of blood pressure was observed. However, there was a significant mean reduction of systolic and diastolic blood pressure between baseline and end-line by around 17mmHg and 8 mmHg, respectively by the intervention group. In conclusion, health education over 6 months was related to significant improvement in blood pressure knowledge and compliance of hypertension patients. Keywords: hypertension patients, health and nutrition education, blood pressure, knowledge, compliance AbstrakDengan tingginya prevalensi hipertensi (25.8% dan 34.1% pada tahun 2013 dan 2018), Indonesia saat ini menghadapi beban ekonomi Kesehatan yang besar dengan diimplementasikannya Jaminan Kesehatan Nasional (JKN). Hal ini disebabkan hipertensi dapat menyebabkan beragam komplikasi kesehatan yang serius dan penurunan produktivitas. Studi ini bertujuan untuk mengevaluasi pengaruh edukasi gizi dan kesehatan terhadap pengetahuan, kepatuhan, dan tekanan darah pasien hipertensi selama 6 bulan pada sebanyak 179 pasien (64%) yang berhasil menyelesaikan rangkaian studi ini (jumlah subjek pada kelompok intervensi = 88 dan jumlah subyek kelompok kontrol = 91). Dibandingkan dengan kelompok kontrol, penderita hipertensi pada kelompok intervensi menunjukkan peningkatan pengetahuan dan kepatuhan yang signifikan (p<0.001), meski tidak ditemukan perbedaan tekanan darah antara kedua kelompok. Meskipun demikian, studi ini menunjukkan adanya penurunan tekanan darah sistolik dan diastolik antara baseline dan endline masing-masing berkisar 17 mmHg dan 8 mmHg. Sebagai kesimpulan, edukasi kesehatan berkaitan dengan peningkatan pengetahuan dan kepatuhan pasien yang signifikan, meski dibutuhkan waktu yang lebih panjang untuk mengobservasi perbedaan tekanan darah antara kedua kelompok.  Kata Kunci: Hipertensi, edukasi gizi dan kesehatan, tekanan darah, pengetahuan, kepatuhan